A comparative study of human IgE binding to proteins of a genetically modified (GM) soybean and six non-GM soybeans grown in multiple locations. (February 2018) - Lu, Mei; Jin, Yuan; Ballmer-Weber, Barbara; Goodman, Richard E.
Abstract: Prior to commercialization, genetically modified (GM) crops are evaluated to determine the allergenicity of the newly expressed protein. Some regulators require an evaluation of endogenous allergens in commonly allergenic crops including soybean to determine if genetic transformation increased endogenous allergen concentrations, even asking for IgE testing using sera from individual sensitized subjects. Little is known about the variability of the expression of endogenous allergens among non-GM varieties or under different environmental conditions. We tested IgE binding to endogenous allergenic proteins in an experimental non-commercial GM line, a non-GM near-isoline control, and five non-GM commercial soybean lines replicated at three geographically separated locations. One-dimensional (1D) and two-dimensional (2D) immunoblotting and ELISA were performed using serum or plasma from eleven soybean allergic patients. The results of immunoblots and ELISA showed no significant differences in IgE binding between the GM line and its non-GM near-isoline control. However, some distinct differences in IgE binding patterns were observed among the non-GM commercial soybean lines and between different locations, highlighting the inherent variability in endogenous allergenic proteins. Understanding the potential variability in the levels of endogenous allergens is necessary to establish a standard of acceptance for GM soybeans compared to non-GM soybean events and lines. Graphical abstract: Image 1 Highlights: Minor differences were found in IgE binding between the GM and non-GM isoline soybeans by immunoblots. Greater IgE binding was noted for three non-GM soybean lines by ELISA. Minor differences were measured in some geographical replicate samples of commercial soybeans. Understanding the variability of IgE binding to endogenous allergens in commercial varieties is essential to understand risks.